DETERMINAN KUALITAS LAPORAN KEUANGAN KOPERASI WANITA DI KABUPATEN SUMENEP - Nurjannah, Evira Afif; Nawirah, Nawirah (Jurnal Riset Akuntansi Politala, 2024)
This research aims to test the influence of understanding SAK ETAP cooperative accounting, the quality of human resources, education level, the use of information technology and integrity on the quality of financial reports of women’s cooperatives in Sumenep district. With this research, it is expected to be additional information and input for women’s cooperatives to further improve the quality of their financial statements. This study builds on previous research by adding integrity variables and object used by the Sumenep Regency women’s cooperative because. The population of this study is a women’s cooperative registered in the KEMENKOPUKM with a sample of 74 respondents and analysis data using SPSS 26.0 software. The results of this study are variables of understanding accounting for SAK ETAP cooperatives and the quality of human resources have positive and significant effect on the quality of financial statements, while the level of education, the use of information technology and integrity do not affect the quality of financial statements in women’s cooperatives.